Impact of social conflicts and fiscal centralization on fiscal efficiency and governance of subnational governments in Peru, 2016–2023 - Morales Rocha, José Luis; Lauracio Ticona, Teófilo; Coyla Zela, Mario Aurelio; Ramos Rojas, Jarol Teófilo; Serruto Medina, Genciana; Vargas Torres, Nakaday Irazema; Zeballos Hurtado, Nilton Juan (Frontiers in Political Science, 2025)
The objective of this article was to explore the impact of social conflict and fiscal centralism on the efficiency and fiscal governance of Peruvian sub-national governments between 2016 and 2023, a period of extreme political instability and social conflict. Data was collected from disaggregated official sources for the 24 departments and the provinces of Lima and Callao. The results were: the effectiveness of public spending by subnational governments has a limited impact on the development and welfare of the populations of the regions. Even in contexts without social conflict, subnational governments are unlikely to achieve effective governance or fiscal autonomy, due to contradictory state policies on fiscal decentralization. Despite the fiscal centralism reflected in administrative and technical practices, local governments are trying to improve their fiscal governance processes.